Stable field effect surface passivation of n-type Cz silicon - Bonilla, R; Wilshaw, P (2013)
Surface recombination of carriers in solar cells can cause a significant reduction in their efficiency and is most commonly minimized by the deposition of surface dielectric layers which simultaneously perform two functions; efficient passivation of surface recombination and the provision of an effective anti-reflection layer. This can be difficult to achieve in practice since the conditions that produce an optimum anti-reflection coating are not necessarily the same as those required for effective passivation. In this work we describe the use of external electrical charging of dielectric layers which serves to improve their passivation properties without affecting their reflection properties. This provides a method by which, to some extent, the electrical and optical properties of the films can be decoupled so allowing better overall performance to be achieved. It is demonstrated that SiO2 and SiO 2/SiN stacks deposited on a silicon surface can provide a stable reduction of surface recombination when chemically treated, electrically charged using a corona discharge and then annealed at low temperature. Surface recombination velocity upper limits of 19 cm/s and 16 cm/s were inferred for single and double layers respectively on n-type, 5 Ωcm, Cz-Si. © 2013 The Authors.